Pareiorhaphis vetula, a new armored catfish from the headwaters of the Rio Doce basin, Brazil (Siluriformes: Loricariidae) - Pereira, Edson H. L.; Lehmann, Pablo A.; Reis, Roberto E. (Zootaxa, 2016)
A new species of Pareiorhaphis is described from the upper Rio Doce basin. The description is based on a series of specimens recently collected in small headwater tributaries to the Rio Guanhães, a tributary of the Rio Santo Antonio, left bank of the Rio Doce in Minas Gerais State, eastern Brazil. Pareiorhaphis vetula, new species, is a small loricariid catfish with dark brown spots irregularly scattered over a brown background on the dorsal surface of body and along flanks. The new species differs from all other Pareiorhaphis species by having the maxillary barbel completely adnate to the lower lip and by adult males possessing a particularly elongate, sharply pointed, conical urogenital papilla. In addition, Pareiorhaphis vetula is further distinguished from most congeners by having a shorter pelvic-fin spine, or by possessing more numerous premaxillary teeth, and by lacking a dorsal-fin spinelet. A comparison with congeners P. nasuta, P. scutula and P. proskynita, which also occur in headwater streams of the Rio Doce basin is also presented.